2018
DOI: 10.1002/psp4.12302
|View full text |Cite|
|
Sign up to set email alerts
|

Study Design Selection in Early Clinical Anti‐Hyperglycemic Drug Development: A Simulation Study of Glucose Tolerance Tests

Abstract: In antidiabetic drug development, phase I studies usually involve short‐term glucose provocations. Multiple designs are available for these provocations (e.g., meal tolerance tests (MTTs) and graded glucose infusions (GGIs)). With a highly nonlinear, complex system as the glucose homeostasis, the various provocations will contribute with different information offering a rich choice. Here, we investigate the most appropriate study design in phase I for several hypothetical mechanisms of action of a study drug. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In contrast, the latter non-model-based approaches conventionally only consider one single time point of the concentration-or effect-time profile (8). The utility of clinical trial simulations and model-based data analysis methods to inform the design of clinical studies has been demonstrated across various therapeutic fields (9)(10)(11). In pharmacogenomics, pharmacometric models have foremost been used to enhance the understanding of the impact of genetic variants on drug exposure and various outcomes rather than for clinical trial design.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the latter non-model-based approaches conventionally only consider one single time point of the concentration-or effect-time profile (8). The utility of clinical trial simulations and model-based data analysis methods to inform the design of clinical studies has been demonstrated across various therapeutic fields (9)(10)(11). In pharmacogenomics, pharmacometric models have foremost been used to enhance the understanding of the impact of genetic variants on drug exposure and various outcomes rather than for clinical trial design.…”
Section: Introductionmentioning
confidence: 99%
“…Also, when simulating with the IMM and estimating with both models, ΔOFV Bias was lower for the IGI model estimations, as presented in Table I, concluding that the IGI model structural assumptions regarding glucose kinetics were less prone to significant misspecifications. Finally, the magnitude of the IMM glucose sub-model bias peaked to 20% of conditional prediction of glucose, which is a considerably high percentage for such integrated system, and in light of a previous study (14), the utilization of such model in drug development to explore drug effects enhancing glucose disappearance will result in the misleading conclusions of overestimating drug effects on insulin-independent glucose clearance and underestimating drug effects on insulin-dependent glucose clearance.…”
Section: Discussionmentioning
confidence: 82%
“…Upon glucose administration, insulin first-phase amount enters insulin first-phase compartment as a system response, then it is released into the insulin central compartment. The IGI model has been widely used in diabetes modeling with applications in exploring drug effects (12), disease progression (13), designing early clinical trials (14), and optimizing IVGTT design (15).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…One of the appealing features of the IGI model is its ability to distinguish hepatic glucose production from glucose disappearance, facilitated by access to labelled glucose measurements during its development. The model had been successfully applied for exploring drug effects (17), disease progression (18), designing early clinical trials (19) and optimizing IVGTT design (20).…”
Section: Nlme Modelsmentioning
confidence: 99%